Mosquito densovirus significantly reduces the vector susceptibility to dengue virus serotype 2 in Aedes albopictus mosquitoes (Diptera: Culicidae) - Ling Kong; Jie Xiao; Lu Yang; Yuan Sui; Duoquan Wang; Shaoqiang Chen; Peiwen Liu; Xiao-Guang Chen; Jinbao Gu (BMC, 2023)
Abstract Background Dengue virus (DENV) is a major public health threat, with Aedes albopictus being the confirmed vector responsible for dengue epidemics in Guangzhou, China. Mosquito densoviruses (MDVs) are pathogenic mosquito-specific viruses, and a novel MDV was previously isolated from Ae. albopictus in Guangzhou. This study aims to determine the prevalence of MDVs in wild Ae. albopictus populations and investigate their potential interactions with DENV and impact on vector susceptibility for DENV. Methods The prevalence of MDV in wild mosquitoes in China was investigated using open access sequencing data and PCR detection in Ae. albopictus in Guangzhou. The viral infection rate and titers in MDV-persistent C6/36 cells were evaluated at 12, 24, 48, 72, 96, and 120 h post infection (hpi) by indirect immunofluorescence assay (IFA) and real time quantitative PCR (RT-qPCR). The midgut infection rate (MIR), dissemination rate (DR), and salivary gland infection rate (SGIR) in various tissues of MDV-infected mosquitoes were detected and quantified at 0, 5, 10, and 15 days post infection (dpi) by RT-PCR and RT-qPCR. The chi-square test evaluated dengue virus serotype 2 (DENV-2) and Aedes aegypti densovirus (AaeDV) infection rates and related indices in mosquitoes, while Tukey's LSD and t-tests compared viral titers in C6/36 cells and tissues over time. Results The results revealed a relatively wide distribution of MDVs in Aedes, Culex, and Anopheles mosquitoes in China and an over 68% positive rate. In vitro, significant reductions in DENV-2 titers in supernatant at 120 hpi, and an apparent decrease in DENV-2-positive cells at 96 and 120 hpi were observed. In vivo, DENV-2 in the ovaries and salivary glands was first detected at 10 dpi in both monoinfected and superinfected Ae. albopictus females, while MDV superinfection with DENV-2 suppressed the salivary gland infection rate at 15 dpi. DENV-2 titer in the ovary and salivary glands of Ae. albopictus was reduced in superinfected mosquitoes at 15 dpi. Conclusions MDVs is widespread in natural mosquito populations, and replication of DENV-2 is suppressed in MDV-infected Ae. albopictus, thus reducing vector susceptibility to DENV-2. Our study supports the hypothesis that MDVs may contribute to reducing transmission of DENV and provides an alternative strategy for mosquito-transmitted disease control. Graphical abstract